Research on characteristics and geological genesis of large-scale deep-seated landslide in tuff formation - Xue, Mengqi; Xu, Guangli; Yao, Feixiang; Ma, Zhuo (Frontiers in Earth Science, 2024)
In engineering practice, engineers generally treated tuff as a lumpy material with a poorly defined laminated structure and a rock group that was not susceptible to slide failure. Most studies of tuff landslides had focused on small clastic landslides in shallow strata with weathering boundaries and lithologic interfaces as slip surfaces. This paper takes a large-scale, deep-seated tuff landslide on the southeast coast of China as the research project. We used borehole TV imaging and exploration tunnels to confirm the material composition and structural characteristics of the tuff stratum and used exploration tunnels to expose the slip soil directly. Microscopic identification, mineralogical composition analysis, zircon U-Pb isotope dating, and Hf isotope analysis of slip soils collected from the exploration tunnels elucidated the geologic background and genesis of the large-scale deep-seated landslides in the tuff stratum. It was found that the formation of a tuff stratum in the landslide area was caused by multi-volcanic orogeny and multi-phase tectonics. The timing of the melting of the original magma from these volcanic events also differs. During these intervals between eruptions, deposition occurred, and this sedimentary material formed the slip soil.